Evaluasi Intensitas Pencahayaan Berdasarkan SNI 7062:2019 dan SNI 7391:2008 pada Perusahaan Suku Cadang Otomotif - Egyt Yusuf Hidayat; Sahipul Ernada; Diva Arianti; Moch. Luqman Ashari (Pusat Riset dan Inovasi Nasional, 2025)
This study evaluates the lighting intensity in an automotive parts manufacturing company in East Java, focusing on compliance with SNI 7062:2019 and SNI 7391:2008 standards. This study addresses the critical industrial hygiene-related issue of inadequate lighting experienced by workers, which can lead to health risks such as eyestrain and increased accident rates. The methodology used was quantitative, involving direct observation and measurement using a calibrated lux meter. The data collected was analyzed through the Anticipation, Recognition, Evaluation and Control (AREP) method to assess the existing lighting conditions and their impact on worker safety and comfort. Findings show that current lighting levels do not meet set standards, highlighting the need for improvements in the working environment. Recommendations for improving lighting conditions are provided to ensure compliance with safety regulations and to promote employee well-being. This research emphasizes the importance of proper lighting in manufacturing settings, contributing to the wider discourse on occupational health and safety in the automotive industry.